Coconut mite, Acathrix trymatus (Keifer) - W. C. Welbourn (EDIS, 2004)
Acathrix trymatus was originally described by Keifer (1962b) from specimens collected in the folds of newly emerging coconut fronds in the Philippines. Keifer's generic name, Acathrix, means "short seta" for the minute scapular setae on the prodorsal sclerite of this species (Keifer 1962b). Briones (1963) investigated A. trymatus and three other eriophyid species on Philippine coconut palms and found their feeding did little damage and did not transmit cadang-cadang disease. This document is EENY-194 (originally published as DPI Entomology Circular 383), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2001.